2015
DOI: 10.1016/j.molcel.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Distinct but Concerted Roles of ATR, DNA-PK, and Chk1 in Countering Replication Stress during S Phase

Abstract: The ATR-Chk1 pathway is critical for DNA damage responses and cell cycle progression. Chk1 inhibition is more deleterious to cycling cells than ATR inhibition, raising questions about ATR and Chk1 functions in the absence of extrinsic replication stress. Here, we show that a key role of ATR in S phase is to coordinate RRM2 accumulation and origin firing. ATR inhibitor (ATRi) induces massive ssDNA accumulation and replication catastrophe in a fraction of early S-phase cells. In other S-phase cells, however, ATR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
305
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(340 citation statements)
references
References 69 publications
(96 reference statements)
33
305
1
1
Order By: Relevance
“…2A and B). We next checked the effects of AZD7762 treatment on DNA damage signaling in H1299 cells and found that treatment induced DNA damage signaling through ATM, likely due to aberrant DNA replication during S phase (34). Treatment of irradiated H1299 cells with AZD7762 did not markedly affect ATM signaling (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…2A and B). We next checked the effects of AZD7762 treatment on DNA damage signaling in H1299 cells and found that treatment induced DNA damage signaling through ATM, likely due to aberrant DNA replication during S phase (34). Treatment of irradiated H1299 cells with AZD7762 did not markedly affect ATM signaling (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Firstly, inhibition of ATR kinase in unperturbed cells induces aberrant origin firing leading to accumulation of chromatin-bound RPA1 and RPA2 ( Figure 1D, lane 3 vs. 15) [22,23]. This RPA accumulation, however, was prevented upon co-treatment with DDKi ( Figure 1D, lane 15 vs. 18) consistent with the essential role of DDK in origin firing.…”
Section: (Supplementarymentioning
confidence: 53%
“…This is likely to be part of a mechanism of coping with the dNTP depletion through RRM2 accumulation. The reduction in E2F1 levels in the CHK1i-treated CHK1i-hypersensitive cell lines are likely to result in reduced RRM2 levels as reported previously (Buisson et al, 2015), and reduced dNTP levels, thus mimicking the effect of HU in reducing cellular dNTP levels. The D20, BL, MM96L and MM329 cell lines were also the ones with the greatest reduction in the non-phosphorylated RPA2 band …”
Section: Chk1i Promotes Rpa2 Hyper-phosphorylation In Chk1i-hypersenssupporting
confidence: 63%
“…Moreover, normal cell types are not killed with siRNA -mediated CHK1 depletion at concentrations that inhibited CHK1 functions (Brooks et al, 2013, Cho et al, 2005. Nevertheless, CHK1 inhibition is effective in sensitising cells to the agents which promotes DNA damage and replication stress, and CHK1 inhibition alone caused cell death in cancer cells with defective DNA repair pathways and high level of replication stress (Brooks et al, 2013, Chen et al, 2009, Buisson et al, 2015.…”
Section: Introductionmentioning
confidence: 99%